Implementing non-tax state revenue in Indonesia: Governance challenges under SDGS - Firmansyah, Amrie; Wibowo, Puji (WIM Solusi Prima, 2025)
Non-Tax State Revenue (PNBP) is a key instrument for development financing and public financial management in Indonesia. Despite significant regulatory strengthening in recent years, audit evidence suggests that challenges in PNBP implementation persist as structural and recurring issues. This study analyzes the implementation of PNBP policies during the 2020–2024 period using the Semester Audit Summary Reports (Ikhtisar Hasil Pemeriksaan Semester-IHPS) issued by the Audit Board of Indonesia as the primary data source. The study applies qualitative content analysis to audit findings and recommendations related to PNBP management. The analysis focuses on governance issues that repeatedly emerge across audit periods, utilizing the Sustainable Development Goals (SDGs) as an interpretive framework to assess the relevance of these findings to institutional strengthening and domestic resource mobilization. The results identify persistent implementation challenges, including low compliance with revenue collection and remittance obligations, weaknesses in internal control systems, repeated audit recommendations due to inadequate follow-up, and fragmented PNBP management across ministries and agencies. These findings suggest that the primary obstacles to effective PNBP implementation are not rooted in regulatory deficiencies, but rather in inconsistent and weak policy implementation at the institutional level. From an SDGs perspective, the implementation challenges of PNBP are closely associated with the agenda of strengthening effective, accountable, and transparent public institutions, as well as improving domestic resource mobilization for development financing. Accordingly, the contribution of PNBP to sustainable development is better understood through improvements in governance quality and fiscal accountability, rather than solely through quantitative increases in non-tax revenue.